System Modeling and Management of Water Resources in Ingulets Basin - Demchuk, Olena; Kovalchuk, Pavlo; Kovalenko, Roman; Kovalchuk, Volodymyr; Balykhina, Hanna (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
Mathematical models have been developed for managing the water resources of the Ingulets River in accordance with the requirements of the EU Water Framework Directive on the establishment of cost-effective water use with ensuring good or excellent ecological river status. The structural and functional diagram of the system model includes the subsystems: water supply by the Dnipro-Ingulets canal; flushing the Ingulets River from the Karachunivske reservoir and displacing the saline prism into the Dnipro River; environmental safety when discharging pollution into the river Ingulets; water supply for irrigation in the Ingulets irrigation system, prevention of soil salinization. Integrated management is carried out by subsystems, by types of management and by a system of criteria. A system of economic and environmental criteria for evaluating integrated management by the basin principle has been developed. Simulation of scenarios based on operational management is carried out. Scenarios are optimized according to the Pareto principle. An example of evaluating the effectiveness of the proposed control system and its comparison with the existing regulations for flushing the Ingulets River is given.